The contestation of Islamic legal thought: Dayah’s jurists and PTKIN’s jurists in responding to global issues - Danial Danial; Munadi Usman; Nur Sari Dewi (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
This study aims to understand the contestation of Islamic legal thought between the scientific tradition of Dayah (Islamic boarding school) and the State Islamic Higher Education Institutions (PTKIN) in responding to global issues. The main data sources in this research are words and actions, the rest are additional data such as documents. Methods of data collection included interviews, observation, and documentation. All data obtained were analyzed by data reduction, analysis, and interpretation. Based on the objectives and research methods above, it was found that there were three factors causing the emergence of contestation between the two Islamic educational institutions, namely, (1) the different methodologies and approaches to Islamic law used; (2) the difference in the spirit of fiction between Dayah and PTKIN. Dayah has the spirit of preserving fiqh, while PTKIN’s spirit is fiqh renewal; (3) Political background. The contestation between Dayah and PTKIN occurred in two areas, namely the area of worship and non-worship. Based on the references, methods of reasoning, approach, and spirit possessed by these two Islamic educational institutions, it can be understood that the two models of Islamic legal thought have the potential to be integrated. Such integration may include; integration of foundations, sources, methods, approaches, and reasoning models.